2003
DOI: 10.1002/anie.200250235
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Cluster Degradation by the Transition of B‐DNA into A‐DNA and the Formation of Nanowires

Abstract: Interactions between metals and biomacromolecules including proteins, polysaccharides, and nucleic acids are important since they can be essential for a number of natural and industrial phenomena. These range from interactions of highly specific metal cofactors with particular proteins [1] to biosorption of heavy metals by polysaccharide hydrogels.[2]The unique features of DNA have been exploited in the development of novel materials, especially in the areas of medicine and nanotechnology. Classical research c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 32 publications
3
69
0
Order By: Relevance
“…Later it was shown that an assembly of the Au-nanoparticles is accompanied by formation of planar superstructure consisting of repetitive neighboring linear DNA molecules and Aunanopartices. These results unequivocally show that linear, rigid, ds DNA molecules after interaction with Aunanoparticles form planar superstructures of type (…-Au-DNA-Au-DNA-Au-DNA-Au-…), despite the anisotropic properties of initial ds DNA molecules [4,[26][27][28][29].…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Later it was shown that an assembly of the Au-nanoparticles is accompanied by formation of planar superstructure consisting of repetitive neighboring linear DNA molecules and Aunanopartices. These results unequivocally show that linear, rigid, ds DNA molecules after interaction with Aunanoparticles form planar superstructures of type (…-Au-DNA-Au-DNA-Au-DNA-Au-…), despite the anisotropic properties of initial ds DNA molecules [4,[26][27][28][29].…”
Section: Resultsmentioning
confidence: 63%
“…For instance, it was suggested that biological effect of Au-nanoparticles on spatially organized double-stranded (ds) DNA structures in vitro and in vivo is similar to the effect of mutagenic molecules [2,3]. One can stress that the interaction of metal nanoparticles with native single-or double-stranded nucleic acid molecules is a well-known phenomenon [4]. Although, the cytotoxicity of Au-nanoparticles in vitro and in vivo has been examined by several research groups, no general conclusion can be drawn at present [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…11 Liu et al 12 found that bare Au 55 (Ph 2 PC 6 H 4 SO 3 H) 12 Cl 6 combined irreversibly into the major grooves of B-DNA (depth: 0.9 nm; length: 1.43 nm) due to their distinct size of 1.4 nm. Subsequently, Tsoli et al 13 reported that the IC 50 (half maximal inhibitory concentration) of Au 55 (Ph 2 PC 6 H 4 SO 3 H) 12 Cl 6 was approximately 180 times lower than the anticancer drug cisplatin in BLM melanoma cells and more than 200 times lower in the MV3 cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Along with this, the reduced toxicity, which was observed in the presence of excess ligand (TPPMS), is a consequence of preventing ligand exchange by interacting the gold cluster core with intracellular biological compounds. Liu et al 2003).…”
Section: (A) Cytotoxicitymentioning
confidence: 99%